Genome-wide identification of key genes related to chloride ion (Cl−) channels and transporters in response to salt stress in birch - Xiuyan Bian; Tao Xie; Jiying Chen; Chunxu Li; Dandan Yin; Wenbo Zhang (BMC Genomics)
Abstract Background Soil salinization is a common matter of concern all over the world, which severely affects plant production, soil health, and ecosystem stability. Birch is a significant afforestation tree species with great ecological, economic, and evolutionary value. It is an excellent model system for studying the acclimation and adaptation of woody plants to extreme environmental conditions due to the current advancements in genomics, genetic variability, and extensive studies with a focus on various biotic and abiotic stresses. To date, the genetic regulation of birch trees in defending against environmental stimuli, particularly salt stress, has made great progress. However, the information on how genes related to chloride ion (Cl−) channels and transporters respond to salt stress remains poorly understood in birch. Results Herein, we performed the genome-wide identification, evolutionary relationship, sequence analysis, and expression patterns of seven family genes encoding Cl− channels or transporters in birch. We identified one, one, four, seven, 13, 56, and 67 genes belonging to the cation chloride co-transporter (CCC) family, bestrophin family, slow type anion channel (SLAC) family, chloride channel (CLC) family, aluminum-activated malate transporter (ALMT) family, nitrate transporter 1/peptide transporter family (NPF) family, and multidrug and toxic compound extrusion (MATE ) family, respectively. Except for motif prediction, a high similarity of the conserved domain composition, gene structures, and physicochemical properties was observed within each group of a certain gene family. Gene Ontology (GO) classification analysis showed that the genes encoding ALMTs, CCCs, CLCs, MATEs, NPFs, and SLACs were mainly involved in ion transport. Transcriptome profiles showed that there were 52 genes related to Cl− transporters and channels differentially expressed in any tissue of the two birch species subjected to salt treatment. Of these, three genes, designated as BpCLCa/b, BpDTX45, and BpDTX18/19, were simultaneously expressed at altered levels in all tissues of the two birch species, which was consistent with the results of quantitative real-time polymerase chain reaction (RT-qPCR) assay. In addition, the molecular docking simulations showed that sodium ion (Na+) and Cl−, respectively, had a strong binding affinity towards BpCLCa/b, BpDTX45, and BpDTX18/19. Conclusion A total of 149 genes related to Cl− channels and transporters were identified from the birch genome. We proposed BpCLCa/b, BpDTX45, and BpDTX18/19 as ion channels or transporters in controlling ionic homeostasis during salt stress response. The findings of our study can provide valuable resources for genetic improvement of salt-tolerant birch varieties for high-quality plantation forests in harsh environments.